Independent release of oxytocin and vasopressin during parturition in the rabbit - Haldar, Jaya (1970)
1. Oxytocin and vasopressin were assayed in samples of blood collected from seven conscious rabbits during parturition. 2. Oxytocin was detected in the blood in ten out of fourteen samples collected during the expulsion of one or more foetuses. Four samples contained 6-100 μu./ml., three 100-200 μu./ml. and three 200-500 μu./ml. 3. Vasopressin was detected in six blood samples collected during the delivery of foetuses but in only one experiment did the amount exceed that found in the corresponding control sample collected before or after delivery. 4. When both hormones were detected in the same blood sample, the ratio of oxytocin to vasopressin varied from 5:1 to at least 26:1. 5. It is concluded that, while oxytocin may not be essential for parturition in the rabbit, stretching of the birth canal during the expulsion of foetuses normally acts as a stimulus for the reflex release of oxytocin from the neurohypophysis and that oxytocin is released independently of vasopressin.